Disentangling electron- and electric-field-induced ring-closing reactions in a diarylethene derivative on Ag(1 1 1). (13th June 2017) - Reecht, Gaël; Lotze, Christian; Sysoiev, Dmytro; Huhn, Thomas; Franke, Katharina J
Abstract: Using scanning tunneling microscopy and spectroscopy we investigate the adsorption properties and ring-closing reaction of a diarylethene derivative (C5F-4Py) on a Ag(1 1 1) surface. We identify an electron-induced reaction mechanism, with a quantum yield varying from 10 −14 –10 −9 per electron upon variation of the bias voltage from 1–2 V. We ascribe the drastic increase in switching efficiency to a resonant enhancement upon tunneling through molecular orbitals. Additionally, we resolve the ring-closing reaction even in the absence of a current passing through the molecule. In this case the electric-field can modify the reaction barrier, leading to a finite switching probability at 4.8 K. A detailed analysis of the switching events shows that a simple plate-capacitor model for the tip-surface junction is insufficient to explain the distance dependence of the switching voltage. Instead, describing the tip as a sphere is in agreement with the findings. We resolve small differences in the adsorption configuration of the closed isomer, when comparing the electron- and field-induced switching product.